A 'R-to-H' Mesh Adaptation Approach for Moving Immersed Complex Geometries Using Parallel Computers. Issue 7 (13th September 2020) - Daldoul, W.; Hachem, E.; Mesri, Y.
ABSTRACT: In this work, we propose an efficient 'r-to-h' adaptation algorithm for moving boundary problems using only vertex displacements and some local h-adaptation operations. Moving boundary algorithms usually require the regeneration of the mesh to avoid his invalidation in particular when the motion is large and/or several bodies are involved. The proposed approach aims to move the mesh nodes, using the Inverse Distance Weighting interpolation method, while conserving the mesh connectivity until the mesh elements quality deteriorate. At this point, a selective h-adaptation involving local mesh modifications such as edge flipping, local refinement and local coarsening are performed only on the submeshes containing badly shaped elements. The developed approach is valid for multi-body simulations and is able to handle their simultaneous independent displacements. The algorithm implemented is extended to parallel computers to speed-up large 3D moving geometries.